Career characteristics and postgraduate education of female dentist graduates of the College of Dentistry at King Saud University, Saudi Arabia - Yousef H. Al-Dlaigan; Sahar F. AlBarakati; Fadheelah Al-Habeeb; Manar Al-Hulaily (Elsevier, 2012)
Objectives: The aims of this study were to investigate the number of female bachelor of dental surgery graduates who earned postgraduate education degrees from King Saud University, their specialties, degrees of qualification, and countries of graduation. Methods: A questionnaire survey was conducted through face-to-face or phone interview among 677 female dentists who graduated from the College of Dentistry at King Saud University between 1984 and 2006. Results: Five hundred forty-five (81%) graduate female dentists responded, of whom 54% had completed postgraduate dental education. In the Saudi Board, 17% had obtained degrees in advanced restorative dentistry, 15% in pediatric dentistry, 14% in advanced general dentistry, 11% in orthodontics, 10% in prosthodontics, 8% in operative dentistry, 5% in endodontics, 5% in periodontics, 3% in oral and maxillofacial surgery, and 11% in other specialties. Fifty-nine percent had master's degrees, 7% had doctorates, 32% had board certificates, and 2% had fellowship certificates. Conclusion: More than half (54%) the female dentists surveyed had pursued postgraduate education. This investigation highlighted the different specialties enrolled by female dentists. Orthodontic post graduate program displayed the highest percentage of interest. Understanding the unavoidable social family needs and the demand for higher education by female dentists provides ideas as more programs should be planned to accommodate the needs of Saudi female dentists. This type of study should be repeated due to the increasing interest of female dentists in higher education. Keywords: Postgraduate, Specialties, Qualification, Education, Dental, Career